SIRT1 exerts protective effects by inhibiting endoplasmic reticulum stress and NF-κB signaling pathways - Zhao, Kaixuan; Zhang, Haoyue; Yang, Dong (Frontiers in Cell and Developmental Biology, 2024)
Silent information regulator 2 homolog 1 (SIRT1), an NAD+-dependent histone deacetylase, plays a pivotal regulatory role in a myriad of physiological processes. A growing body of evidence suggests that SIRT1 can exert protective effects in metabolic disorders and neurodegenerative diseases by inhibiting endoplasmic reticulum (ER) stress and the nuclear factor-κB (NF-κB) inflammatory signaling pathway. This review systematically elucidates the molecular mechanisms and biological significance of SIRT1 in regulating ER stress and the NF-κB pathway. On one hand, SIRT1 can deacetylate key molecules in the ER stress pathway, such as glucose-regulated protein 78 (GRP78), X-box binding protein 1 (XBP1), PKR-like ER kinase (PERK), inositol-requiring enzyme 1α (IRE1α), and activating transcription factor 6 (ATF6), thereby alleviating ER stress. On the other hand, SIRT1 can directly or indirectly remove the acetylation modification of the NF-κB p65 subunit, inhibiting its transcriptional activity and thus attenuating inflammatory responses. Through these mechanisms, SIRT1 can ameliorate insulin resistance in metabolic diseases, exert cardioprotective effects in ischemia-reperfusion injury, and reduce neuronal damage in neurodegenerative diseases. However, it is important to note that while these findings are promising, the complex nature of the biological systems involved warrants further investigation to fully unravel the intricacies of SIRT1's regulatory mechanisms. Nevertheless, understanding the regulatory mechanisms of SIRT1 on ER stress and the NF-κB pathway is of great significance for expanding our knowledge of the pathogenesis of related diseases and exploring new preventive and therapeutic strategies targeting SIRT1.